The combination of the opioid glycopeptide MMP-2200 and a NMDA receptor antagonist reduced l-DOPA-induced dyskinesia and MMP-2200 by itself reduced dopamine receptor 2-like agonist-induced dyskinesia. (October 2018) - Flores, Andrew J.; Bartlett, Mitchell J.; Root, Brandon K.; Parent, Kate L.; Heien, Michael L.; Porreca, Frank; Polt, Robin; Sherman, Scott J.; Falk, Torsten
Abstract: Dopamine (DA)-replacement therapy utilizingl -DOPA is the gold standard symptomatic treatment for Parkinson's disease (PD). A critical complication of this therapy is the development ofl -DOPA-induced dyskinesia (LID). The endogenous opioid peptides, including enkephalins and dynorphin, are co-transmitters of dopaminergic, GABAergic, and glutamatergic transmission in the direct and indirect striatal output pathways disrupted in PD, and alterations in expression levels of these peptides and their precursors have been implicated in LID genesis and expression. We have previously shown that the opioid glycopeptide drug MMP-2200 (a.k.a. Lactomorphin), a glycosylated derivative of Leu-enkephalin mediates potent behavioral effects in two rodent models of striatal DA depletion. In this study, the mixed mu-delta agonist MMP-2200 was investigated in standard preclinical rodent models of PD and of LID to evaluate its effects on abnormal involuntary movements (AIMs). MMP-2200 showed antiparkinsonian activity, while increasingl -DOPA-induced limb, axial, and oral (LAO) AIMs by ∼10%, and had no effect on dopamine receptor 1 (D1 R)-induced LAO AIMs. In contrast, it markedly reduced dopamine receptor 2 (D2 R)-like-induced LAO AIMs. The locomotor AIMs were reduced by MMP-2200 in all three conditions. The N -methyl- d -aspartate receptor (NMDAR) antagonist MK-801 has previously been shown to be anti-dyskinetic, but only at doses that induce parkinsonism. When MMP-2200 was co-administered with MK-801, MK-801-induced pro-parkinsonian activity was suppressed, while a robust anti-dyskinetic effect remained. In summary, the opioid glycopeptide MMP-2200 reduced AIMs induced by a D2 R-like agonist, and MMP-2200 modified the effect of MK-801 to result in a potent reduction ofl -DOPA-induced AIMs without induction of parkinsonism. Highlights: The opioid glycopetide MMP-2200 has modest antiparkinsonian activity. MMP-2200 reduces dyskinesia induced by activation of D2R-like dopamine receptors. The NMDA receptor antagonist MK-801 is anti-dyskinetic, but also pro-parkinsonian. MMP-2200 + MK-801 reducesl -DOPA-induced dyskinesia. MMP-2200 does suppress the pro-parkinsonian activity of MK-801.